REVIEW JURNAL : PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN - Epan Saputra; Omariah; Maysella; Junengsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Organizational culture is one of the most important factors influencing organizational success in achieving its objectives. Organizational culture serves as a system of values, norms, beliefs, and behaviors that guide organizational members in carrying out their duties and responsibilities. This literature review aims to analyze the influence of organizational culture on employee performance based on previous studies. The method used is a literature study by reviewing relevant national and international journals. The findings indicate that a strong and positive organizational culture can improve employee productivity, commitment, motivation, loyalty, and work quality. Furthermore, organizational culture plays a significant role in creating a conducive work environment that enhances both individual and organizational performance. These findings suggest that organizations need to establish and maintain adaptive, innovative, and achievement-oriented cultures to improve employee performance sustainably.